PREVENTIVE MAINTENANCE MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE II PADA FASILITAS PRODUKSI KRITIS PERUSAHAAN BAJA - Ramadhania, Sherin; Dewantara, Achmad Samudra; Permata, Nia Sastra; Suroso, Muhammad Suryo Panotogomo Abi (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
One of the largest steel industries in Indonesia produces cold-rolled sheet steel, with production handled by the Cold Rolling Mill Factory. This study focuses on the Continuous Pickling Line and Continuous Tandem Cold Mill units, which have the highest downtime of 230 hours, resulting in a delay cost of 6 billion Rupiah. The objective is to identify the functions, failures, causes, and impacts on critical components, and to propose appropriate maintenance activities and intervals. Failure information is gathered using failure mode and effect analysis (FMEA), while the appropriate maintenance activities are determined using a reliability-centered maintenance II decision worksheet. The study identifies four critical components in the CPL unit and five in the CTCM unit. Five failure modes are addressed by on-condition scheduling, seven by restoration scheduling, and seven by failure interval. Proposed maintenance intervals for on-condition scheduling include 9,413 minutes for stand #5, 8,371 minutes for stand #4, 12,383 minutes for stand #3, 12,996 minutes for stand #2, and 7,123 minutes for stand #1. Restoration scheduling intervals are 34,000 minutes for the saddle breaker, 21,000 minutes for the wiper, and between 12,000–23,000 minutes for other components. Failure interval maintenance for the welder, pickling tank, and stands ranges from 2,409 to 6,540 minutes.